2022
DOI: 10.3390/ijms23136982
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Effects of Fostamatinib in Combination with Conventional Antiplatelet Drugs

Abstract: New antithrombotic medications with less effect on haemostasis are needed for the long-term treatment of acute coronary syndromes (ACS). The platelet receptor glycoprotein VI (GPVI) is critical in atherothrombosis, mediating platelet activation at atherosclerotic plaque. The inhibition of spleen tyrosine kinase (Syk) has been shown to block GPVI-mediated platelet function. The aim of our study was to investigate if the Syk inhibitor fostamatinib could be repurposed as an antiplatelet drug, either alone or in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Our network shows the anti-platelet effects offostamatinib via its targets in addition to SYK and we computationally and experimentally validated its inhibitory effect on SYK and SFKs. Its effects through SYK have been shown before as interfering with thrombosis but not with hemostasis (78,79) and its potential use in COVID-19 has also been suggested by a computational study that confirmed fostamatinib's targets by molecular docking (80). It was shown to counteract the platelet hyperactivity in vitro on platelets from COVID-19 patients with potentially actionable pathways as central for platelet activation and/ or vascular complications (81).…”
Section: Drug Effects On Platelet Control: Fostamatinib and Beyondmentioning
confidence: 97%
“…Our network shows the anti-platelet effects offostamatinib via its targets in addition to SYK and we computationally and experimentally validated its inhibitory effect on SYK and SFKs. Its effects through SYK have been shown before as interfering with thrombosis but not with hemostasis (78,79) and its potential use in COVID-19 has also been suggested by a computational study that confirmed fostamatinib's targets by molecular docking (80). It was shown to counteract the platelet hyperactivity in vitro on platelets from COVID-19 patients with potentially actionable pathways as central for platelet activation and/ or vascular complications (81).…”
Section: Drug Effects On Platelet Control: Fostamatinib and Beyondmentioning
confidence: 97%
“…There was also noticeable improvement in microperfusion in the ischaemic area after reperfusion ( Pachel et al, 2016 ). It has not been possible to find a small molecule inhibitor of GPVI, but novel antagonists have now been produced (described in the following paragraphs) and it is also possible to block GPVI-mediated platelet responses by inhibition of Btk and Syk which are part of its downstream signalling pathway ( Harbi et al, 2022 ; Harbi et al, 2021 ; Smith et al, 2022 ).…”
Section: Clinical Assessment Of Microvascular Thrombosis During Stemimentioning
confidence: 99%
“…Fostamatinib may therefore be a drug to consider for patients with an increased thrombotic risk, such as those with coronary artery disease, diabetes, advanced age or obesity. Indeed, in a recent in vitro study, R406 had synergistic effects with existing antiplatelet agents on atherosclerotic plaque-induced platelet activation [86].…”
Section: Fostamatinib and Thromboembolic Eventsmentioning
confidence: 99%